The dynamics of entrepreneurial careers in high-tech ventures experience, education, and exit - Cumming, Douglas J.; Walz, Uwe 1962-; Werth, Jochen (SAFE, Sustainable Architecture for Finance in Europe, 2016)
We investigate the career dynamics of high-tech entrepreneurs by analyzing the exit choice of entrepreneurs: to found another firm, to become dependently employed, or to act as a business angel. Our detailed data resting on the CrunchBase online database indicate that founders stick with entrepreneurship as a serial entrepreneur or as an angel investor only in cases where the founder (1) had experience either in founding other startups or working for a startup, (2) had a ‘jack-of-all-trades’ education, or (3) achieved substantial financial success upon a venture capital exit transaction.